APLIKASI INPUT NILAI MAHASISWA FAKULTAS TEKNOLOGI INFORMASI UNISBANK BERBASIS ANDROID (Information Technology and Telematics, 2014)
ABSTRACTsemakin berkembang pesat, faktaini dapat dibuktikan denganberkembangnya berbagai jenissmartphones yg di buat vendorvendorponsel terkemuka di dunia.Hal ini baik secaralangsungmaupuntidaklangsungberpengaruhterhadapperkembanganduniapendidikan diIndonesia dalammengembangkanberbagai macamteknologi.Android sendiri adalah namasebuah perusahaan yang bergerakdalam bidang teknologi informasikhususnya software dengan namaperusahaan Android Inc. yangdidirikan pada bulan Oktober 2003di Palo Alto, California, AmerikaSerikta.Para pendirinya adalahIn line with the development oftechnologies that exist today, people want to getinformation faster and easier access toinformation. One of them University in Semarang,which is Unisbank. In Unisbank, lecturer in theinput valuesof students still use the web. In thiscase, the lecturer must input the values using thecomputer. To facilitate faculty Unisbank the valueof student input, so in this study were made viaandroid based applications.The purpose of this research is to designand build an android -based application that canbe used to facilitate the user in entering studentgrades through the Faculty of InformationTechnology Unisbank android. In this research,the writer used the prototype. For theprogramming language, the authors use the Javaprogramming language eclipse and MySQLdatabase .This study resulted in an application thatcan simplify the input values in the input valuesUnisbank faculty students. This application can berun on mobile devices that have android operatingsystem.Keywords :Input values, the input valuesapplications, android applications.